2002
DOI: 10.1210/jc.87.5.2367
|View full text |Cite
|
Sign up to set email alerts
|

Cosecretion of Estrogen and Inhibin B by a Feminizing Adrenocortical Adenoma: Impact on Gonadotropin Secretion

Abstract: We describe the first reported case of a feminizing adrenocortical adenoma cosecreting estrogens and inhibin B. A 39-yr-old man, with no previous history of disease and free of treatment, complained of gynecomastia without any clinical abnormality. Plasma E2 and T were 496 pmol/liter and 8.7 nmol/liter, respectively. Testicular echography was normal, and abdominal computed tomography scan showed a 28-mm right adrenal tumor. hCG (5000 IU, im) induced a rise in plasma T levels (20.7 nmol/liter) without any chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The proaC form of inhibin thus constitutes a novel and specific serum tumor marker for ACC. In contrast, serum inhibin A and B levels did not differ between patient groups, although three ACC patients did have increased serum levels of inhibin B, as was previously described in two case reports (38,39).…”
Section: Discussionsupporting
confidence: 72%
“…The proaC form of inhibin thus constitutes a novel and specific serum tumor marker for ACC. In contrast, serum inhibin A and B levels did not differ between patient groups, although three ACC patients did have increased serum levels of inhibin B, as was previously described in two case reports (38,39).…”
Section: Discussionsupporting
confidence: 72%
“…To our knowledge, there is a single adrenal adenoma described in the literature in which E 2 and inhibin B cosecretion was determined [10]. The patient described in that study presentedafeminizing adrenocortical tumor and the pathological examination confirmed an adenoma.…”
Section: Discussionmentioning
confidence: 89%
“…Gonadotropin secretion may be modified in some adrenocortical carcinoma cases with functioning lesions, in the presence of excessive tumor testosterone or estrogen production. In the rare adrenocortical tumor cases described with excessive tumor estrogen production, gonadotropin levels were reported as being suppressed [9, 10, 18]. Bouraïma et al [18] described a patient with a feminizing adrenocortical adenoma, wherein LH and FSH pulsatility was completely abolished, indicating the fundamental participation of E 2 in the control of gonadotropin secretion, although the inhibin was not investigated in this case.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Inhibin production by adrenocortical cortisol-or estrogen-secreting tumors has been observed in vivo (219,220,221). The main endocrine consequence of this process is inhibition of pituitary FSH release (219,220). It is not known whether inhibin may also affect tumor steroidogenesis through paracrine mechanisms or not.…”
Section: Factorsmentioning
confidence: 99%